Deciding Death: Capital Punishment in America - Meskin, Darja M. (My University, 2018)
American comedian Dan Miller once said that “the death penalty is becoming a way of life in this country.” With more than 1,400 executions and over 150 death row exonerations since 1973, it’s hard to disagree with him1. As more and more people are exonerated from death row each year, it is important to once again question the constitutional validity of the death penalty. It is becoming increasingly clearer that the death penalty, especially implemented as a deterrent, is becoming obsolete. Not only is it obsolete, but without an absolute guarantee of guilt, regrettably cruel as well. In this paper, I will argue that the United States government lacks the legitimate authority to execute criminals via capital punishment due to the arbitrary influence of race in capital sentencing. For the purposes of this paper, I will assume that the death penalty is morally permissible and that the Eighth Amendment does not, on its own, rule out capital punishment. The focus of my paper will be that, in light of the Fourteenth Amendment, the state fails to respect the equal status of African-Americans in capital sentencing and that this failure compromises the state’s legitimacy in implementing capital punishment, thereby making capital punishment unconstitutional under the Due Process and Equal Protection clauses of the Fourteenth Amendment.